Two peas in a pod - Mlynowski, Sarah (New York : Scholastic Press, 2018)
Abby is feeling slighted by not being chosen festival leader at school, and her brother Jonah thinks that a trip through the magic mirror is just what she needs--but when they find themselves in a strange version of the Princess and the pea, and Abby is tagged as the princess, who will be the next ruler of the Kingdom of Bog (which is very damp and infested with alligators), she is not so much complimented as desperate to find an alternate princess, and get herself and her brother home.
4.9
3-6
500L
Keywords: Magic mirrors -- Fiction; Brothers and sisters -- Fiction; Characters in literature -- Fiction; Magic -- Fiction; Brothers and sisters -- Fiction; Princesses -- Fiction; Fairy tales